Pelatihan Alat Evaluasi Berbasis HOTS Bagi Guru MGMP Daring dan Pemasaran Kabupaten Magetan - Sudarwanto, Tri; Harti; Saino; Sulistyowati, Raya (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2022)
An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.